1998
DOI: 10.1121/1.422130
|View full text |Cite
|
Sign up to set email alerts
|

The effects of organic compound doping in single-bubble sonoluminescence

Abstract: Single-bubble sonoluminescence (SBSL) in water has been studied in the presence of low concentrations of simple organic compounds. For a given concentration of aliphatic alcohol, the degree of quenching follows the order, ethanol< I -propanol< 1-butanol, Preliminary experiments with simple we& acids and bases indicate that SBSL quenching only occurs when the pH is adjusted such that the solutes are in their neutral form. me results obtained indicate that the extent of SBSL quenching, by the solutes used, is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1999
1999
2000
2000

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…Also, an increase in the alkyl chain length of the alcohol results in a more pronounced effect on the reduction in the sonoluminescence signal. These trends have also been observed in single-bubble sonoluminescence experiments indicating they are not specific to multibubble systems …”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Also, an increase in the alkyl chain length of the alcohol results in a more pronounced effect on the reduction in the sonoluminescence signal. These trends have also been observed in single-bubble sonoluminescence experiments indicating they are not specific to multibubble systems …”
Section: Resultssupporting
confidence: 55%
“…In our previous work on sonochemistry , and sonoluminescence , processes in aqueous solutions, we have been concerned with the effects that surface-active solutes have on the two ultrasound-generated phenomena. It was found that the additives can dramatically affect the extent of certain sonochemical reactions as well as enhance or quench the sonoluminescence.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanism i can be discounted because SL quenching, using the same additives as in the present study, has also been observed in single bubble experiments . Furthermore, when the solute adsorbed at the bubble/water interface is charged, no quenching takes place.…”
Section: Discussionsupporting
confidence: 59%
“…SL, both SBSL and MBSL, is also known to be affected by the presence of solutes in the liquid. Small amounts of water-soluble organic solutes, such as aliphatic alcohols, amines, and carboxylic acids, induce quite strong SL quenching. The effect has been shown to be linked to the amount of solute adsorbed to the bubble/solution interface, and with the additional requirement that the solute be volatile .…”
Section: Introductionmentioning
confidence: 99%